2009
DOI: 10.1086/595285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of De‐ and Rehydration in Desiccation‐Tolerant Liverworts: A Cytological and Physiological Study

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Chicago Press is collaborating with JSTOR to digitize, preserve and extend access to International Journal of Plant Sciences.Liverworts are probably the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 58 publications
3
40
0
Order By: Relevance
“…In chloronemata, these changes and subsequent recovery closely resemble those in leaf cells of mosses (Tucker et al, 1975;Proctor et al, 2007b), liverworts (Pressel et al, 2009), pteridophytes (Platt et al, 1997) and angiosperms (Gaff et al, 1976;Gaff, 1997;Dalla Vecchia et al, 1998); In caulonemata, instead, there are remarkable similarities to FCCs (Pressel et al, 2006). Although some of the ultrastructural changes elicited by dehydration can simply be ascribed to the general withdrawal of water from the cells and are, indeed, also observed in fast-desiccated cells that do not recover following rehydration, for example close packing of free ribosomes, reduction in the volume of plastids and mitochondria, and chromatin condensation in the nuclei, others are clearly indicative of more active processes.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In chloronemata, these changes and subsequent recovery closely resemble those in leaf cells of mosses (Tucker et al, 1975;Proctor et al, 2007b), liverworts (Pressel et al, 2009), pteridophytes (Platt et al, 1997) and angiosperms (Gaff et al, 1976;Gaff, 1997;Dalla Vecchia et al, 1998); In caulonemata, instead, there are remarkable similarities to FCCs (Pressel et al, 2006). Although some of the ultrastructural changes elicited by dehydration can simply be ascribed to the general withdrawal of water from the cells and are, indeed, also observed in fast-desiccated cells that do not recover following rehydration, for example close packing of free ribosomes, reduction in the volume of plastids and mitochondria, and chromatin condensation in the nuclei, others are clearly indicative of more active processes.…”
Section: Discussionmentioning
confidence: 68%
“…The same is also true for the meristematic cells of Po. formosum (Pressel et al, 2006) and those of the liverwort Southbya nigrella (Pressel et al, 2009). Changes in MT dynamics have also been described in higher plants in response to cold and freezing stress (Pressel et al, 2006 and references therein), and Wang et al (2007) have shown recently that salt tolerance in Arabidopsis requires the reorganization of the cortical MTs.…”
Section: Introductionmentioning
confidence: 96%
“…This "resaturation respiration" is different from basal respiration; it is cyanide sensitive in the lichen Hypogymnia physodes (and perhaps generally), which basal (dark) respiration is not, and decays in a comparable time that it takes for the fine structural changes to be completed (Farrar and Smith 1976;Proctor et al 2007a). Recovery from desiccation takes place regardless of the presence of protein synthesis inhibitors (Proctor and Smirnoff 2000;Proctor et al 2007a, b;Pressel et al 2009). The pattern of protein synthesis alters dramatically in the first hours following rewetting, and the sequence of events during recovery is complex (Oliver 2009).…”
Section: Recovery From Desiccationmentioning
confidence: 99%
“…The pattern of protein synthesis alters dramatically in the first hours following rewetting, and the sequence of events during recovery is complex (Oliver 2009). Morphological change at the subcellular level is most active in the first few hours of rehydration, but full return of organelles to their pre-desiccation form and disposition, and reassembly of the cytoskeleton may take 24-48 h (Pressel et al 2006(Pressel et al , 2009. This is essential for active translocation (Ligrone and Duckett 1994;Pressel et al 2006) and for the cell cycle, cell division, and cell growth (Mansour and Hallet 1981), but apparently not for photosynthesis or carbon fixation (Pressel et al 2009).…”
Section: Recovery From Desiccationmentioning
confidence: 99%
See 1 more Smart Citation